SINEKTIK TERPIMPIN BERWAWASAN LINGKUNGAN: SOLUSI INOVATIF UNTUK MENGASAH KREATIVITAS PUISI DAN KEPEDULIAN LINGKUNGAN SISWA KELAS V SDN MANISREJO 01 MADIUN - Dian Widiyawati; Jeffry Handhika; Muh. Waskito Ardhi (An Nafi': Multidisciplinary Science, 2026)
The integration of environmental awareness into creative writing learning is a relevant effort to respond to global ecological issues. This study aims to describe the implementation of the Guided Synectic model based on the local environment as an innovative solution to simultaneously enhance poetry writing skills and environmental care attitudes among fifth-grade students. This qualitative classroom action research was conducted in two cycles at SDN Manisrejo 01 Madiun. Data were collected through participatory observation, poetry writing tests, attitude scale questionnaires, interviews, and analysis of student work. The results indicate that the environment-based Guided Synectic model successfully created a meaningful learning context. The stages of synectic (creating analogies between environmental objects and poetic elements) guided students to produce more imaginative and concrete poetry. Furthermore, direct interaction with the environment and discussions about local ecological issues significantly increased students' awareness and positive attitudes toward environmental sustainability. This study concludes that the Guided Synectic model, when integrated with environmental content, can function as an effective dual-purpose pedagogical strategy: honing literary creativity and cultivating environmental character from an early age.